2011
DOI: 10.3390/ijms12117410
|View full text |Cite
|
Sign up to set email alerts
|

A Sandwich Electrochemical Immunosensor Using Magnetic DNA Nanoprobes for Carcinoembryonic Antigen

Abstract: A novel magnetic nanoparticle-based electrochemical immunoassay of carcinoembryonic antigen (CEA) was designed as a model using CEA antibody-functionalized magnetic beads [DNA/Fe3O4/ZrO2; Fe3O4 (core)/ZrO2 (shell) nano particles (ZMPs)] as immunosensing probes. To design the immunoassay, the CEA antibody and O-phenylenediamine (OPD) were initially immobilized on a chitosan/nano gold composite membrane on a glassy carbon electrode (GCE/CS-nano Au), which was used for CEA recognition. Then, horseradish peroxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…An additional 10 healthy and 10 gastric cancer patients were used for external validation of the diagnostic model, and the sensitivity and specificity were up to 90%. CEA is glycosyl phosphatidyl inositol cell-surfaceanchored glycoproteins which are usually at very low levels in healthy adults and upregulated in many kinds of cancers [14,15]. CEA is usually used as a biomarker for many kinds of cancers, such as colorectal cancer [16,17] and gastric carcinoma [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 10 healthy and 10 gastric cancer patients were used for external validation of the diagnostic model, and the sensitivity and specificity were up to 90%. CEA is glycosyl phosphatidyl inositol cell-surfaceanchored glycoproteins which are usually at very low levels in healthy adults and upregulated in many kinds of cancers [14,15]. CEA is usually used as a biomarker for many kinds of cancers, such as colorectal cancer [16,17] and gastric carcinoma [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…CEA is glycosyl phosphatidyl inositol cell-surface-anchored glycoproteins which are usually at very low levels in healthy adults and upregulated in many kinds of cancers [ 14 , 15 ]. CEA is usually used as a biomarker for many kinds of cancers, such as colorectal cancer [ 16 , 17 ] and gastric carcinoma [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…[163] Carcinoembryonic antigen (CEA) is a set of glycoproteins highly related to cell adhesion, which are normally produced during fetal development but stopped before birth. [164] Consequently, the CEA level is usually very low in healthy adults' blood but increased in some types of cancer, which means that it can be used as a tumor target in cancer targeting therapy. Tiernan et al [165] reported fluorescent dye-doped silica NPs and rare earth doped UCNPs conjugated with targeted anti-CEA Ab for cancer targeting imaging and therapy.…”
Section: Antibody-mediated Targetingmentioning
confidence: 99%
“…Electrochemical ELISA has the added advantage of not being affected by particles, chromophores, and fluorophores that might be present in a sample and which might cause interference with optical detection. [9][10][11] However, a simpler method for developing a convenient, stable and sensitive electrochemical ELISA still requires significant research.…”
Section: Introductionmentioning
confidence: 99%